2007
DOI: 10.1128/mcb.00494-07
|View full text |Cite
|
Sign up to set email alerts
|

Role for Histone Deacetylase 1 in Human Tumor Cell Proliferation

Abstract: Posttranslational modifications of core histones are central to the regulation of gene expression. Histone deacetylases (HDACs) repress transcription by deacetylating histones, and class I HDACs have a crucial role in mouse, Xenopus laevis, zebra fish, and Caenorhabditis elegans development. The role of individual class I HDACs in tumor cell proliferation was investigated using RNA interference-mediated protein knockdown. We show here that in the absence of HDAC1 cells can arrest either at the G 1 phase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
187
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 57 publications
11
187
0
3
Order By: Relevance
“…Last, we tested whether HDAC1/2 knockdown affects c-Myc expression in K562 cells. Consistent with a previous report (25), c-Myc expression increased upon loss of either HDAC1 or HDAC2 but not HDAC3 (Fig. 6E).…”
Section: Tip60 Interacts With C-myb-tip60supporting
confidence: 81%
“…Last, we tested whether HDAC1/2 knockdown affects c-Myc expression in K562 cells. Consistent with a previous report (25), c-Myc expression increased upon loss of either HDAC1 or HDAC2 but not HDAC3 (Fig. 6E).…”
Section: Tip60 Interacts With C-myb-tip60supporting
confidence: 81%
“…Previous reports demonstrated that class I HDACs are recruited by Sp1 to the p21 WAF1/Cip1 promoter (Lagger et al, 2002;Huang et al, 2005;Wilson et al, 2006;Senese et al, 2007;Spurling et al, 2008). Our findings identify HDAC4 as a new component of the Sp1-dependent repressor complex on the p21 WAF1/Cip1 promoter.…”
Section: Discussionsupporting
confidence: 58%
“…However, most HDAC inhibitors are global and nonspecific for the various HDAC isoforms. Class I HDACs regulate p21 WAF1/Cip1 gene expression (Huang et al, 2005(Huang et al, , 2006Wilson et al, 2006;Senese et al, 2007;Spurling et al, 2008), but it is not known whether other HDACs are involved.…”
Section: Introductionmentioning
confidence: 99%
“…siRNA studies have been crucial to understanding the importance of individual isoforms of class I HDACs and have helped characterize their function in proliferation and tumorigenesis (Wilson et al, 2006;Spurling et al, 2008;Weichert et al, 2008b), including HDAC-1 (Glaser et al, 2003;Inoue et al, 2006;Senese et al, 2007). In this study, we report that knockdown of HDAC-1, either by miR-449a or synthetic HDAC-1 siRNA, results in cell-cycle arrest, a senescent-like phenotype and loss of clonogenicity in PC-3 cells.…”
Section: Discussionmentioning
confidence: 79%